Overall Survival with Amivantamab-Lazertinib in EGFR-Mutated Advanced NSCLC - Yang, James Chih-Hsin; Lu, Shun; Hayashi, Hidetoshi; Felip, Enriqueta; Spira, Alexander I.; Girard, Nicolas; Kim, Yu Jung; Lee, Se-Hoon; Ostapenko, Yurii; Danchaivijitr, Pongwut; Liu, Baogang; Alip, Adlinda; et al. (The New England journal of medicine, 2025)
In advanced non-small-cell lung cancer with EGFR mutations, amivantamab-lazertinib led to longer overall survival than osimertinib but was associated with an increased risk of adverse events of grade 3 or higher.